Shmuel's bridge : following the tracks to Auschwitz with my survivor father - Sommer, Jason (Imagine!, 2022)
"A memoir recounting the author's trip with his survivor father to Eastern Europe to locate the bridge where his uncle was killed on the way to Auschwitz"--